Cowpea cultivar mixtures for stable and optimal leaf and seed yields in a maize intercropping system - Kabululu, MS; Ojiewo, Christopher Ochieng; Oluoch, M; Maass, Brigitte L. (Informa UK Limited, 2014)
Cowpea [Vigna unguiculata (L.) Walp.] is an important crop in many African countries, though its use as a leafy vegetable has not received adequate research attention. Leaf and grain yields are low and unstable, especially in highly variable climates in marginal areas. A study was conducted to evaluate the impact of cowpea cultivar mixtures on leaf and seed yield and stability in a cowpea–maize (Zea mays L.) intercropping system. Four cowpea cultivars and a local landrace check were used in monoculture or in different mixture levels. When leaves were harvested, seed yield was reduced on average by 57% and 59%, on-station and on-farm, respectively, with large variation among treatments. The local landrace check had the highest leaf yields on-farm where it produced a mean of 25 g/plant/2-weekly harvesting interval. It also conveyed positive mixture effects; however, yield stability across successive harvests was lowest, indicating its capacity to react to positive environmental changes. Some mixtures of more than two cultivars maintained more leaf yield stability over time across successive leaf harvests. The highest positive relative mixture effects on leaf and seed yields of up to 100% and 193%, respectively, were obtained in two-way mixtures, indicating that these may offer the best combinations for improved yields and to screen for favorable and unfavorable cultivar components.